Intramolecularly double-donor-stabilized stannylene and its coordination towards Ag(I) and Au(I) centers - Chibde, Purva; Raut, Ravindra K.; Kumar, Vikas; Deb, Rahul; Gonnade, Rajesh; Majumdar, Moumita (Chemistry-An Asian Journal, 2021)
The intramolecularly double-donor-stabilized stannylene 1 has been synthesized from the salt-metathesis reaction between two equivalents of lithium pyridine ene-amide L1 and SnCl2. Compound 1 exhibits dipolar behavior when reacted with B(C6F5)(3) leading to the zwitterionic compound 2. The reaction of 1 with one equivalent and 0.5 equivalent of AgOTf (OTf=trifluoromethane sulfonate) result in the formation of a stannylene-AgOTf complex 3 and a homoleptic distannylene-silver ionic complex 4, respectively. Analogous to complex 4, the gold(I) complex 5 has been synthesized from the reaction between two equivalents of 1 and 0.5 equivalent of AuCl.SMe2/Me3SiOTf. Complex 5 is the first example of homoleptic stannylene-Au(I) ionic complex among the very scarce reports on stannylene-gold(I) coordination complexes. All compounds have been structurally characterized using single crystal X-ray crystallography. Solution-state characterization have been performed using multinuclear NMR techniques. Detailed DFT calculations on the optimized geometries 1 o, 3 o-5 o reveal the change in sp- hybridization on the pyramidal Sn(II) center upon metal coordination and their bonding overlaps.
Keywords: coordination; gold cation; hybridization; intramolecular donor; stannylene

Zwitterionic tetrastanna(II) cyclic crown - Sahoo, Padmini; Chibde, Purva; Das, Satyabrata; Banerjee, Subhrashis; Mali, Bhupendra P.; Vanka, Kumar; Gonnade, Rajesh G.; Yildiz, Cem. B.; Majumdar, Moumita (European Journal of Inorganic Chemistry, 2023)
A 12-membered zwitterionic tetrastanna(II) cycle 1 having a crown ether-like topology has been isolated from the deprotonation of 1,1 & PRIME;-methylenediimidazole (B) with two equivalents of Sn[N(SiMe3)(2)](2) (A). The solid-state structure and NMR analysis confirms the tetrastanna(II) cycle 1 to be comprised of two stannate(II) and two stannyliumylidene ion pairs in alternating positions of the heterocycle. Computational analysis shows greater nucleophilicity at the proximally located stannate(II) centers. Nonetheless, the tetrastanna(II) cycle 1 remains poorly reactive due to engagement of Sn-II lone pair electrons in intramolecular donor-acceptor interactions. Simple deprotonation reaction between Sn[N(SiMe3)(2)](2) (A) and N-(diisopropylphenyl)imidazole (C) in equimolar ratio has led to a stannylene 2, involving the formation of a Sn-C covalent bond with the anionic imidazol-2-yl carbon center along with the release of NH(SiMe3)(2). Compound 2 exists as a dimer, where the unsubstituted ring nitrogen atom coordinated intermolecularly to the other stannylene center.
Keywords: Deprotonation; Imidazole; Macrocycle; Sn-II cation; stannylene